Tinjauan Hukum Terhadap Pelanggaran Tata Ruang Dalam Pembangunan Perumahan Di Kawasan Perkotaan - Safira Insanidya; Aqila Dina Vismara; Aurellia Rahma Juwita; Laely Hasna Fatikha (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The rapid growth of urban areas in Indonesia has led to an increase in housing demand, which often results in spatial planning violations. This research aims to review the legal framework governing spatial utilization control, identify types of violations in housing development, and analyze the applicable legal sanctions. This study employs a normative judicial research method, analyzing relevant laws and regulations such as Law No. 26 of 2007 on Spatial Planning, as amended by Law No. 6 of 2023, and Government Regulation No. 21 of 2021. The findings indicate that dominant spatial violations include development inconsistent with Regional Spatial Plans (RTRW), the conversion of green open spaces and protected areas, and construction without proper building approvals (PBG). These violations lead to environmental degradation, increased flood risks, and social conflicts. Legal enforcement is carried out through administrative sanctions (warnings, fines, or demolition), civil lawsuits for unlawful acts, and criminal penalties including imprisonment and fines. Despite comprehensive regulations, implementation remains hindered by weak government supervision and lack of inter-institutional coordination. Therefore, strengthening oversight and consistent law enforcement are essential to achieve orderly, safe, and sustainable urban development.